2020
DOI: 10.1016/j.socscimed.2020.113019
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy is strongly associated with distrust of conventional medicine, and only weakly associated with trust in alternative medicine

Abstract: It is well established that people who use complementary and alternative medicines (CAM) are, on the whole, more vaccine hesitant. One possible conclusion that can be drawn from this is that trusting CAM results in people becoming more vaccine hesitant. An alternative possibility is that vaccine hesitancy and use of CAM are both downstream consequences of a third factor: distrust in conventional treatments. To examine this, we measured vaccine hesitancy and CAM use in a representative sample of Spanish residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 30 publications
7
69
0
8
Order By: Relevance
“…Although empirical work has not identified a mechanism for this relationship, qualitative work has revealed a common theme among antivaxxers: that Big Pharma has a profit motive to exaggerate the benefits of vaccinations and to disguise their dangers (Hoffman et al, 2019). It appears that many other Western medical treatments are drawn into the gravitational pull of this mistrust: Indeed, mistrust of conventional medicines such as chemotherapy and antidepressants is a bigger predictor of antivaccination attitudes than trust in alternative medicines (Hornsey, Lobera, & Díaz-Catalán, 2020).…”
Section: Conspiracist Worldviewmentioning
confidence: 99%
“…Although empirical work has not identified a mechanism for this relationship, qualitative work has revealed a common theme among antivaxxers: that Big Pharma has a profit motive to exaggerate the benefits of vaccinations and to disguise their dangers (Hoffman et al, 2019). It appears that many other Western medical treatments are drawn into the gravitational pull of this mistrust: Indeed, mistrust of conventional medicines such as chemotherapy and antidepressants is a bigger predictor of antivaccination attitudes than trust in alternative medicines (Hornsey, Lobera, & Díaz-Catalán, 2020).…”
Section: Conspiracist Worldviewmentioning
confidence: 99%
“…For example, a lack of trust between a new mother and her child's pediatrician may play a major role in the decision-making process about vaccination [18]. Distrust appears to be stronger than trust, in that distrust in conventional medicine more strongly predicts vaccine hesitancy than trust in alternative or natural health remedies [36]. The level of information parents have about vaccines may play a large role in winning patient trust [37], and the availability of sound information, including patient-initiated research efforts, can help overcome doubts [38].…”
Section: The Role Of Mistrustmentioning
confidence: 99%
“…Finally, for many of the parents, CAM also represented an expert system that is free from the influence of "Big Pharma" and that stands in opposition to conventional medical epistemology. The relationship between vaccine hesitancy, use of CAM, trust in CAM, and trust in conventional treatments was recently investigated in 5,200 Spanish adults [29]. Even though the results showed that more CAM use was associated with greater vaccine hesitancy, a distrust in conventional treatments played a more important role in explaining vaccine hesitancy than did trust in CAM.…”
Section: Introductionmentioning
confidence: 99%
“…We used structural equation modeling (SEM) to examine if trait reactance predicted vaccination behavior (accepting influenza vaccines for oneself and childhood vaccines for one’s children), vaccine attitudes, and CAM use, and whether these relationships were fully or partially mediated through trust in doctors. Because previous studies have suggested that negative attitudes to vaccines and positive attitudes to CAM are related to reluctance in accepting conventional medicine [ 27 29 , 32 ], we hypothesized that higher trait reactance would predict lower trust in doctors, more negative attitudes to vaccines, a lower likelihood of accepting vaccines and a higher likelihood of using CAM. Finally, we tested the hypothesis that trait reactance and trust in doctors would explain some of the association between the vaccine-related outcomes and CAM use.…”
Section: Introductionmentioning
confidence: 99%